Design of a Co-Working Space Building with a Biomimicry Architecture Concept in Bandar Lampung - K. Alifah; P. Kurniawan; N. Ifadianto (Journal of Engineering and Scientific Research, 2026)
The economic development in Bandar Lampung is becoming increasingly competitive, leading to higher demand and marketing of office spaces as business actors will need new spaces. Therefore, co-working spaces become a beneficial solution in overcoming these challenges, serving as workspaces and venues for collaboration. However, working continuously indoors can cause feelings of boredom and stress. Several workplace studies show that contact with nature experienced at work or in the office can improve health. One approach is to bring the concept of nature into the building through Biomimicry Architecture by adopting the principles of nature's mechanisms. By adopting these principles, Biomimicry Architecture can also help minimize stress levels for workers in the co-working space; thereby, creating a more comfortable working environment and reducing stress. Based on the analysis and design concepts for the co-working space with the biomimicry architecture concept, biomimicry can address issues related to air pollution by adapting nature's mechanisms. The biomimicry concept in the co-working space applies three principles mass composition, interior layout, exterior layout, skin facade, and utility systems in the building.